Lyophyllum decastes-derived polysaccharides alleviate DSS-induced colitis in mice by suppressing inflammation, enhancing intestinal barrier integrity, and restoring gut microbiota homeostasis - Ghaleb, Eslam; Alioui, Yamina; Yazeed, Jamalat; Wahan, Natheer; Bashah, Ahmed; AL-waqeerah, Ali; Atta, Aamna; Sun, Yuxin; Xin, Yi; Wang, Liang; Feng, Bin; Mao, Weifeng (Frontiers in Pharmacology, 2025)
IntroductionInflammatory bowel disease (IBD), including ulcerative colitis (UC), is characterized by disturbances in the intestinal barrier, immune system dysfunction, and an altered gut microbiota composition. Lyophyllum decastes, a medicinal mushroom known for its bioactive polysaccharides, has shown potential anti-inflammatory properties. However, its therapeutic effects on ulcerative colitis have not been studied. This study investigates the effects of L. decastes polysaccharides (LDP) on dextran sulfate sodium (DSS)-induced colitis in mice.MethodsUlcerative colitis was induced in BALB/c mice by administering 3% DSS in drinking water for 7 days. Mice were then treated orally with LDP at doses of 200 or 400 mg/kg for 14 days. Disease activity index (DAI), histopathological analysis, cytokine levels, myeloperoxidase (MPO) activity, tight junction protein expression (occludin and ZO-1), and gut microbiota composition were assessed.Results and discussionLDP treatment significantly reduced DAI scores and preserved colonic histological structure. It modulated cytokine levels, decreasing pro-inflammatory cytokines (TNF-α, IL-6, IL-1β) and increasing anti-inflammatory cytokines (IL-10, IL-4, TGF-β). Additionally, LDP improved intestinal barrier function by reducing MPO activity and enhancing occludin and ZO-1 expression. 16S rRNA sequencing revealed a significant restoration of gut microbiota diversity, with an increase in beneficial bacteria Muribaculaceae, Lactobacillus, and Lachnospiraceae, and a reduction in pathogenic bacteria Escherichia-Shigella. these findings suggest that LDP exhibits therapeutic effects in DSS-induced colitis through anti-inflammatory properties, enhancement of intestinal barrier function, and modulation of gut microbiota. These findings suggest that LDP may serve as a promising novel therapeutic agent for the management of ulcerative colitis.